Grafting from Fluoropolymers Using ATRP: What is Missing?. Issue 4 (28th December 2021) - Guerre, Marc; Semsarilar, Mona; Ladmiral, Vincent
Abstract: Grafting polymers from fluoropolymer backbones is very advantageous to modify the properties of these often non‐functional materials. It is particularly useful in the field of ultrafiltration membranes to tune the hydrophilicity of PVDF membranes and to add other properties such as antifouling for example. One of the main techniques used to effect such grafting is ATRP. A large number of papers are published every year on this topic. However, careful examination of this body of work reveals that the evidence provided to support the covalent bonding of polymer chains on the fluoropolymers are often limited and rather unconvincing. This is of course due to the difficult detection of the rare connecting covalent bonds. Nevertheless, this detection problem is not the only issue. Grafting from fluoropolymers using ATRP relies on the homolytic cleavage of C−F bond, notorious for their high stability and BDE. Moreover, fluoropolymers based on VDF are prone to dehydrofluorination by reaction with bases and nucleophiles, which leads to the formation of unsaturations within the polymer backbone. This reaction is often completely ignored even though ATRP ligands can trigger this elimination. These two very often overlooked reactivity features seriously question the use of ATRP as an efficient grafting technique for fluoropolymers. Abstract : Grafting‐from ATRP protocols using fluoropolymers as substrates are very often used. Actual positive proof that ATRP is the mechanism at work in the grafting or that grafting occurred at all is very scarce. This perspective article gives an overview of the most relevant examples of such protocols as well as possible other mechanisms of grafting.